How does online postal self-sampling (OPSS) shape access to testing for sexually transmitted infections (STIs)? A qualitative study of service users - Tommer Spence; Alison Howarth; David Reid; Jessica Sheringham; Vanessa Apea; David Crundwell; Sara Day; Claire Dewsnap; Louise Jackson; Catherine H. Mercer; Hamish Mohammed; Jonathan D. C. Ross; et al. (BMC, 2024)
Abstract Background Sexually transmitted infections (STIs) are a serious public health issue in many countries. Online postal self-sampling (OPSS) is increasingly used to test for STIs, a trend accelerated by the COVID-19 pandemic. There remains limited understanding of how service users experience OPSS and what leads them to access it over clinic-based services, or vice versa. This research seeks to address these gaps, by undertaking a large qualitative study which sits within the ASSIST study, a mixed-methods, realist evaluation of OPSS. Methods Participants were recruited via clinic-based and online sexual health services in three case study areas in England. Purposive sampling was used to over-represent populations disproportionately affected by poor sexual health: young people; people of colour; men who have sex with men; and trans and non-binary people. Semi-structured interviews were analysed using Levesque's conceptual framework of access to healthcare. Results We interviewed 100 service users. Participants typically became aware of OPSS from sexual health services, the internet or word of mouth. Acceptability of OPSS was facilitated by the perceived privacy it offered over clinic-based services, which some participants found embarrassing to access. OPSS also enabled participants to overcome barriers to reaching clinic-based services, such as a lack of appointment availability, although difficulty obtaining OPSS kits in some areas undermined this. As all services in our case study areas were free to use, affordability did not significantly shape access, although OPSS enabled some participants to avoid costs associated with travelling to clinic-based services. Participants were usually able to engage with OPSS, finding it easy to use and reliable, although blood self-sampling was challenging for most. Participants valued the support offered by clinic-based services beyond STI testing, including the opportunity to access contraception or ask staff questions, and felt this was more appropriate when they had specific concerns about their sexual health, such as STI symptoms. Conclusions Our findings constitute one of the largest qualitative studies to have explored OPSS and offer valuable insights to providers. OPSS shapes access to STI testing in a number of ways, including facilitating access in many circumstances, but users also want to retain access to clinic-based services, particularly for when they believe they need support beyond STI testing.